2016
DOI: 10.1016/j.ijhydene.2016.07.232
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of oxygen vacancies on the electrocatalytic activity of AuTiO2 nanocomposites towards oxygen reduction

Abstract: Functional nanocomposites based on gold nanoparticles deposited onto TiO 2 colloids were prepared by a simple wet chemistry method, and subject to hydrothermal treatment at a controlled temperature in the presence of ascorbic acid. Transmission electron microscopic measurements showed that the gold nanoparticles (10-30 nm in diameter) were embedded within the TiO 2 matrix consisting of colloids of 5-10 nm in diameter and anatase crystalline structures, as evidenced in x-ray diffraction studies. Interestingly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…As suggested by a sharper slope change, SA1 apparently comprises two components with different relaxation rates, which are not observed for A1. The dependence on microwave power of the intensity of signals associated with oxygen vacancy defects in TiO 2 was described either as reaching a plateau 46 or decreasing aer a maximum, 53 indicating relatively long relaxation times for these radicals. The latter trend was also attributed to unpaired electrons in a point defect at the interface between particles.…”
Section: Surface and Electronic Characterizationmentioning
confidence: 99%
“…As suggested by a sharper slope change, SA1 apparently comprises two components with different relaxation rates, which are not observed for A1. The dependence on microwave power of the intensity of signals associated with oxygen vacancy defects in TiO 2 was described either as reaching a plateau 46 or decreasing aer a maximum, 53 indicating relatively long relaxation times for these radicals. The latter trend was also attributed to unpaired electrons in a point defect at the interface between particles.…”
Section: Surface and Electronic Characterizationmentioning
confidence: 99%
“…In spite of this distinctiveness, their poor intrinsic electronic conductivity and inferior bifunctionality for overall electrochemical water splitting have hindered their practical applications [22,23]. To resolve its intrinsic conductivity issue, it was reported while creating oxygen vacancies in these oxides has altered the electronic environment that acted critically to induce conductivity [24][25][26]. Xu et al has fabricated plasma-engraved oxygen vaccines in Co 3 O 4 nanosheets and reported its improved OER performance (η of 300 mV at J OER = 10 mA cm −2 ) over pristine Co 3 O 4 nanosheets (η of 540 mV at J OER = 10 mA cm −2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, a well‐defined resonance emerged at ca . 3370 G after hydrogen treatment, and the resonance became increasingly intensified with increasing thermal treatment temperature from 400 to 600 °C (aqua blue, magenta, and blue curves), with the corresponding g value estimated to be 2.001 . A similar profile was observed without the deposition of Pd nanoparticle (green curve).…”
Section: Resultsmentioning
confidence: 57%